prove
(1 + tanA) ^2 + ( 1- tanA)^2 = 2sec A
Answers
Answered by
4
Hello,
we must show that:
(1+tanA)²+(1-tanA)²=2 sec²A
we consider the first member:
(1+tanA)²+(1-tanA)²
we have that:
(1+tanA)²+(1-tanA)²;
= 1+tan²A+2tanA+1+tan²A-2tanA;
=2+2tan²A
being sen²A-tan²A=1 that is
sec²A=1+tan²A;
so you have:
2+2tan²A;
=2(1+tan²A);
=2sec²A
Hope this helps you ☺️☺️❤️❤️✌️✌️
Answered by
9
hey❤
here is ur answer!!
please refer to the attachment :))
hope it helps!!
thanks☺☺☺
here is ur answer!!
please refer to the attachment :))
hope it helps!!
thanks☺☺☺
Attachments:
![](https://hi-static.z-dn.net/files/d1a/1501cc965fabba03ea1122bb7d564a73.jpg)
Similar questions